Central tower and dome of the BMC building - Ghosh, Ayan (2023)
Till the mid-nineteenth century, public buildings in Mumbai adopted architectural styles popular in Europe. Notable among them were the Neo-Classical and Gothic Revival styles. By the time Frederick W. Stevens started working in Mumbai, in 1869, a new eclectic form was gradually taking shape that incorporated European forms mixed with Indian elements inspired by Hindu and Islamic architecture. This new style came to be known as Indo-Saracenic.